(untitled) (Indian Journal of Animal Production and Management, 2023)
The extent to which the milk production enhancement programmes succeed depends up on the extent to which the dairy husbandry services are delivered effectively to the farmers. Basically, the dairy farmers need three types of (integrated) support: i). Extension and advisory services (EAS) to enrich the knowledge and improve the skills of dairy farmers ii). Availability and accessibility of input service such as semen, vaccines, medicines, equipments, instruments, feed, fodder seeds etc and iii). Delivery of technical service by the veterinarian (Vet) or Para-Veterinarian (Para-Vet). There are many service providers but very little focus on EAS. Ways and means to improve the effectiveness of EAS are indicated.